Gymnasio Mineiro de Uberlandia: o processo de disciplinarização escolar (1937-1945) - Ghantous, Daniella Soraya Resende Araújo (2006)
It is a research about the current Escola Estadual de Uberlândia within the period between 1937 and 1945. The aim of this study is to present the analysis related to culture in the school environment of Gymnasio Mineiro de Uberlandia, by means of the school subjects as a way of settling behavior patterns in the students during Estado Novo . By means of a survey on the taught school subjects and on the behaviors that were valued, it was identified the influence of Brazilian social, political and economical context on the state schools students background, especially Gymnasio Mineiro de Uberlandia; the part played by the school in materialization of the foundation of the State lead by Vargas, the connection between the organization of the school environment and the necessity to separate the genders were laid-out as well as the bodies disciplining and it was observed the influence of the contents of the taught subjects to sculpture the kind of citizen the school should shape. In order to accomplish such analysis, a bibliographical review was made to discuss the part played by educational institutions in the social scenario they belong to. This investigation is also anchored in official documents from Gymnasio Mineiro de Uberlandia correspondent to Estado Novo period and in articles about this institution on the local newspapers A Tribuna e O Reporter. The analysis also considered former teachers , student s and students inspector s statements who experienced the process, within the period 1937-1945. The educational legislations of the state and the country were other documents researched which supported the analysis. It was noticed that the school culture of Gymnasio Mineiro de Uberlandia was connected to a bigger social culture because contributed to shape a disciplined individual. The school environment of Gymnasio Mineiro de Uberlandia was projected to be a teaching, watching, ranking and rewarding machine by means of control and constant, subtle watching of bodies and minds, and mainly of strategic distribution of bodies in the environment. The time, the activities, the behaviors, the speeches, the body and the sexuality of the individuals were all controlled. Even though some students disobeyed the rules and were punished by the gratification-sanction device, which quantified, classified and punished or rewarded the individual, according to his behavior and his performance. This punishment aimed at the deviation reduction however it was verified that the penalties applied to the transgressors did not accomplish their goals thoroughly for there was a lot of resistance. The behaviors of some students were not remodeled and their consciences were not redirected, despite the culture and the school routine of Gymnasio Mineiro de Uberlandia at that time, being propitious to the disciplining of bodies and minds. In opposition to what was taught, some of the knowledge did not work to some students, therefore the existence of negative evaluations results and reprehensions to certain attitudes.